Aerial eyewitness: A pilot study of drone use in journalism - Homburg, Nick Jr. (Kansas State University, 2017)
Unmanned Aerial Systems (UAS), or drones as they are commonly known, could allow journalists to report the news like never before. A drone is a tool with great potential, yet fraught with controversy as the result of its military past. In 2012, the Unmanned Aerial System had become domesticated and could have become the hottest new technology since the cell phone. The first unmanned systems came to service gathering intelligence and in the delivery of lethal and non-lethal payloads for the military. With the domestication of UAS technologies, not only have numerous commercial uses been revealed for the UAS, the drone has made it to the hands of the general public, raising concerns of how this technology is to be used. At the time of this thesis, in the United States, the only legal use of UAS was by hobbyists. Also, at the time of this thesis, the Federal Aviation Administration (FAA) had not provided comprehensive regulations or guidelines regarding the commercial use of UAS platforms (FAA, 2015). Of the many uses purposed for UAS platforms, one use of interest for journalists is the increased potential for newsgathering and surveillance. With UAS/drone technologies becoming increasingly more available, concerns are raised about safety, privacy, context, and the integrity of news source or (conflict of interest). The researcher interviewed working journalists from four major networks with stations located in states mandated as test sites by the FAA. The journalists were asked about their concerns pertaining to the ethical uses of drone for journalistic newsgathering. The interviewsreveled that with proper training, regulations, and common sense the concerns about safety, privacy, context, and conflict of interest could be moderated.
Keywords: Drones